A New View of Meditation - Rubin, Jeffrey B. (Journal of religion and health, 2001)
After years of meditating, are you still saddled with many of the same personal conflicts and interpersonal inhibitions that plagued you before you began? Rubin explores the hidden flaws in the meditative method itself. He explores Buddhism's ambivalent relationship to emotional life, and the negative consequences of "letting go" of experience. Detaching from experience may result in renouncing vital aspects of ourselves, such as constructive passion. The author argues that real meditation is transformative not tranquilizing, fostering a dynamic way of living.